KARAKTER PERSONAL SEBAGAI PEMODERASI PENGARUH PARTISIPASI PENGANGGARAN TERHADAP SENJANGAN ANGGARAN PADA BANK PERKREDITAN RAKYAT - Aristianto Putra, I Kadek Yudi; Dwija Putri, I G. A. M. Asri (E-Jurnal Akuntansi, 2016)
Management participation in the budgeting process tends to cause budgetary slack depending on the interests held by management. The purpose of this study is to determine the effect on the budgetary participation and budgetary slack determine personal character as a variable moderating influence on budgetary slack budgetary participation. This study was conducted in 35 rural credit banks in Badung and each Rural Bank taken three respondents. The data used in this research is primary data obtained directly by distributing questionnaires to 105 respondents using purposive sampling technique. The data analysis technique used in this study are Moderated Regression Analysis (MRA). Results of this study stated that the participation budgeting positive influence on budgetary slack. Pessimistic personal character may moderate the effects of budgetary participation on budgetary slack.
Keywords: Participation Budgeting, Personal Character, Budgetary Slack